Bioinoculants as Promising Complement of Chemical Fertilizers for a More Sustainable Agricultural Practice - Scagliola, Marina; Valentinuzzi, Fabio; Mimmo, Tanja; Cesco, Stefano; Crecchio, Carmine; Pii, Youry (Frontiers in Sustainable Food Systems, 2021)
Plant Growth Promoting Rhizobacteria (PGPR) represent a heterogeneous group of bacteria, which have been characterized for their ability to influence the growth and the fitness of agricultural plants. In the quest of more sustainable practices, PGPR have been suggested as a valid complement for the agronomical practices, since they can influence several biochemical and molecular mechanisms related to the mineral nutrients uptake, the plant pathogens suppression and the phytohormones production. Within the present work, three bacterial strains, namely Enterobacter asburiae BFD160, Pseudomonas koreensis TFD26 and Pseudomonas lini BFS112, previously characterized on the basis of distinctive PGPR traits, were tested to evaluate: i) their persistence in soil microcosms; ii) their effects on seeds germination; iii) their possible influence on biochemical and physiological parameters related to plant growth, fruit quality and plant nutrient acquisition and allocation. To these aims, two microcosms experiments featuring different complexities, i.e. namely a growth chamber and a tunnel, were used to compare the effects of the microbial inoculum to those of chemical fertilization on Cucumis sativus L. plants. In the growth experiment, the Pseudomonas spp. induced positive effects on both growth and physiological parameters; TFD26, in particular, induced an enhanced accumulation of mineral nutrients (Fe, Ca, Mn, Ni, Zn) in plant tissues. In the tunnel experiment, only P. koreensis TFD26 was selected as inoculum for cucumber plants used in combination or in alternative to a chemical fertilizer. Interestingly, the inoculation with TFD26 alone or in combination with half-strength chemical fertilizer could induce similar (e.g. Ca accumulation) or enhanced (e.g. micronutrients concentration in plant tissues and fruits) effects as compared to plants treated with full-strength chemical fertilizers. Overall, the results hereby presented show that the use of PGPR can lead to comparable, and in some cases improved, effects on biochemical and physiological parameters of cucumber plants and fruits. Although these data are referred to experiments carried out in controlled condition, though different from an open filed cultivation, our observations suggest that the application of PGPR and fertilizers mixtures might help shrinking the use of chemical fertilization and potentially leading to a more sustainable agricultural practice.